PENGEMBANGAN PEMAHAMAN SIKAP MODERASI BERAGAMA BERBASIS NILAI INKLUSIVITAS PADA MAHASIWA DI PERGURUAN TINGGI - Hidayatulloh, Taufik; Saumantri, Theguh (Ibn Khaldun University, Bogor, 2023)
This paper is based on the results of a study entitled “Study of the Influence of Paramadina Life Value Lecture (NHP) on Student Character and Behavior”. The study was driven by concerns about rising intolerance and radicalism as well as counterproductive tensions between Islam and nationality among young people and students. This condition of course has the potential to threaten the disintegration of people and the nation in general. From the results of descriptive statistical analysis shows that there is a strong correlation and significant influence between NHP lecture learning and the perception and attitude of students towards Islamic and Indonesian values. This research program is designed by conducting training and workshops for a number of students who have strategic and important in the formation of understanding and moderate religious attitudes. Dissemination of the idea of religious moderation is carried out, among others, through training and development of Islamic values that are one breath with national values (Indonesianness) and socialization of moderate religious understanding is one of the long-term deradicalization strategies at the upstream level.